2012
DOI: 10.1128/mcb.05420-11
|View full text |Cite
|
Sign up to set email alerts
|

Cdk8 Regulates Stability of the Transcription Factor Phd1 To Control Pseudohyphal Differentiation of Saccharomyces cerevisiae

Abstract: The yeast Saccharomyces differentiates into filamentous pseudohyphae when exposed to a poor source of nitrogen in a process involving a collection of transcription factors regulated by nutrient signaling pathways. Phd1 is important for this process in that it regulates expression of most other transcription factors involved in differentiation and can induce filamentation on its own when overproduced. In this article, we show that Phd1 is an unstable protein whose degradation is initiated through phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 47 publications
6
56
0
Order By: Relevance
“…None of the strains containing SSN8 displayed significant enhancement of flocculation over the duration of the time course ( Figure 1B and Figure S1B). However, deleting SSN8 resulted in increased flocculation rates, which is consistent with earlier reports documenting this phenotype (Nelson et al 2003;Raithatha et al 2012). Surprisingly, the histone H3 Lys4 methylation regulators JHD2 and SET1 influenced flocculation in the SSN8 mutant.…”
Section: Ssn8 and Jhd2 Are Required To Inhibit Pseudohyphal Growth Unsupporting
confidence: 91%
See 2 more Smart Citations
“…None of the strains containing SSN8 displayed significant enhancement of flocculation over the duration of the time course ( Figure 1B and Figure S1B). However, deleting SSN8 resulted in increased flocculation rates, which is consistent with earlier reports documenting this phenotype (Nelson et al 2003;Raithatha et al 2012). Surprisingly, the histone H3 Lys4 methylation regulators JHD2 and SET1 influenced flocculation in the SSN8 mutant.…”
Section: Ssn8 and Jhd2 Are Required To Inhibit Pseudohyphal Growth Unsupporting
confidence: 91%
“…Since its identification, the Ssn8p/Ssn3p (Cnc1p/Cdk8p) protein complex has been characterized as both an activator and a repressor of gene transcription, with many molecular targets identified including pol II CTD, other mediator subunits, and transcription factors (Hengartner et al 1995;Chi et al 2001;Nelson et al 2003;Raithatha et al 2012;Nemet et al 2014). Microarray studies of yeast lacking the SSN3 kinase showed that 40% of the 173 genes that were upregulated were also increased during diauxic shift (Holstege et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P sites within the global transcriptional coregulatory Mediator complex were found both in the large-scale data set and in a targeted follow-up study. Cdk8 is the sole kinase component of Mediator, and subsequent in vitro assays identified P sites within Mediator that were phosphorylated by Cdk8 in vitro at sites consistent with the previously described Cdk8 target motif (phospho-S/T-P) (29)(30)(31)(32)(33). This data set gives a first in-depth analysis of the C. albicans phosphoproteome and is the largest fungal phosphopeptide data set at this time.…”
supporting
confidence: 67%
“…In fungi, the roles of MED13 and of the kinase module have been studied most extensively in the yeasts Saccharomyces cerevisiae (Chi et al, 2001;Gonzalez et al, 2014;Krasley et al, 2006;Nelson et al, 2003;Raithatha et al, 2012;Shahi et al, 2010;Singh et al, 2006;van de Peppel et al, 2005), Schizosaccharomyces pombe (Linder et al, 2008;Zhu et al, 2006), and in human and plant pathogens such as Candida albicans (Lindsay et al, 2014;Uwamahoro et al, 2012;Zhang et al, 2013) and Cryptococcus neoformans (Wang et al, 2011). These studies revealed that the kinase module regulates hundreds of genes associated with carbon source utilization, stress responses, morphogenesis, filamentation and adhesion (Blankenship et al, 2010;Bluhm and Woloshuk, 2006;Chang et al, 2004;Cooper et al, 1999;Holstege et al, 1998;Larschan and Winston, 2005;Linder et al, 2008;Samuelsen et al, 2003;Uwamahoro et al, 2012;Wang et al, 2011;Wheeler et al, 2008;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 98%